Review of "The Force of Non-Violence: An Ethico-Political Bind" - Marietta Kosma; Amir Pichhadze (Ideas: Journal of English Literary Studies)
This article reviews "The Force of Non-Violence: An Ethico-Political Bind," written by Judith Butler and published by Verso in 2020.